Removal of Congo red using Vernonia amygdalina leaf powder: optimization, isotherms, kinetics, and thermodynamics studies. Issue 1 (31st December 2022) - Zewde, Dagme; Geremew, Belete
ABSTRACT: Dye effluents generated from industries are the main source of water pollution. The elimination of dyes from water bodies is essential for environmental protection. From an ecological and financial standpoint, the adsorption strategy using low-cost adsorbents is a sensible solution to remove dye pollutants from wastewater. In this study, Vernonia amygdalina leaf powder (VALP) adsorbent was prepared and used to eliminate Congo red dye (CRD) from aqueous solutions. Scanning Electron Microscopy (SEM) and Fourier Transmission Infrared (FT-IR) spectroscopy techniques were used to study VALP morphology as well as the nature of the interaction between VALP and CRD. Batch adsorption experiments were conducted to examine the influence of adsorbent dose, CRD concentration, contact time, and pH on CRD adsorption using VALP. As a result, 0.5 g of adsorbent dose, 100 mg/L CRD solution, 70 minute contact time, and a solution pH of 8 were determined as optimum values. Temkin adsorption isotherm models were used to test the experimental data, and the result is fitted well to the Langmuir model with a maximum adsorption capacity of 57.47 mg/g. Adsorption kinetics models such as pseudo-first-order, pseudo-second-order, and intraparticle diffusion were used to determine adsorption parameters. As a result, pseudo-second-order was fitted well to the experimental data. Thermodynamic parameters such as ΔH° (5.702 kJ/mol) and ΔG° (−1674.6566 to −994.6388 J/ mol) show endothermic and spontaneous adsorption. The current study confirmed that VALP is one of the most effective, eco-friendly, and sustainable dye adsorbents from solution compared to other low-cost adsorbents.